Rapid salivary pepsin test: blinded assessment of test performance in gastroesophageal reflux disease - Saritas Yuksel, Elif; Hong, Shih-Kuang S; Strugala, Vicki; Slaughter, James C; Goutte, Marion; Garrett, C Gaelyn; Dettmar, Peter W; Vaezi, Michael F (The Laryngoscope, 2012)
Pepsin lateral flow device (LFD) is a rapid noninvasive test to detect salivary pepsin as a surrogate marker for gastroesophageal reflux disease (GERD). We aimed to establish the test sensitivity, specificity, positive and negative predictive values (PPV, NPV) in patients with symptomatic and objective evidence of GERD compared to healthy controls. Prospective, blinded, controlled cohort study. A total of 230 samples were analyzed. In vitro bench testing was conducted on 52 gastric juice and 54 sterile water samples to assess test sensitivity and specificity. Saliva was collected from 58 patients with GERD and 51 controls. All patients with GERD underwent esophagogastroduodenoscopy (EGD) and wireless 48-hour pH monitoring off acid suppressive therapy. PPV and NPV were calculated based on disease definition of esophagitis and/or abnormal pH monitoring. Receiver operating characteristics analysis of in vitro samples found assay sensitivity and a specificity of 87%. There were 6/51 (12%) control subjects and 13/58 (22%) patients with GERD who tested positive for salivary pepsin (P = .25). There was a step-wise increase in the prevalence of positive salivary pepsin: esophagitis (55%), abnormal pH monitoring (43%), GERD symptoms only (24%) (P < .001). Salivary pepsin test showed a PPV of 81% and NPV of 78% for those with objective evidence of GERD (abnormal pH and/or esophagitis). Rapid LFD for salivary pepsin has acceptable test characteristics in patients with GERD. A positive salivary pepsin test in this group may obviate the need for more expensive diagnostic testing by EGD or pH monitoring.